Ponysitters club : fun at the fair [videorecording (DVD)] - Kimmel, Neale Elizabeth; Casimiri, Luciano; Neundorf, Morgan; Punnewaert, Cailan; Chrisman, Diana; Wilson, Hugh (Actor); Leon, Madeline; Carson, Victoria (Dreamscape kids series., 2024)
Excited about the Fall Fair, the Ponysitters are busy with a multitude of preparations. The Fair also brings out a competitive nature in some of the contestants, but nothing works better than teamwork.